Synthesis and Effectiveness of a Novel Food Safety Toolkit for Low-Literacy Novice Food Handlers - Karla M. Acosta; Alberto A. Beiza; Isabella Raschke; Zhihong Lin; Juan M. Madera; Mary Dawson; Zenaida Aguirre-Muñoz; Sujata A. Sirsat (Journal of Food Protection)
The state of Texas announced a requirement for all foodservice employees to pursue an American National Standards Institute (ANSI) certified food handler training in September 2016. However, the effectiveness of ANSI-certified food safety training for low-literacy novice food handlers has not been investigated. Low-literacy novice food handlers are those who have some familiarity with the field but may not have the literacy level or may have a language barrier that is as an obstacle to completing the training and/or certification. This study aimed to develop a novel food safety training toolkit (NTK) as a supplementary resource to existing ANSI-certified training tools and evaluate its effectiveness in improving food handlers’ knowledge retention and certification. To achieve this, a mixed-method study was conducted. For the first part of the research, one-on-one interviews were conducted with foodservice stakeholders (managers, sanitarians, owners) to identify the gaps and needs that exist in the current food safety training system. In the second part of the research, NTK was synthesized and designed with clear illustrations and drawings based on previous education and training literature. A between-subjects experiment was conducted to assess the effectiveness of NTK on food handlers’ food safety knowledge. Results showed that the participants’ overall food safety knowledge significantly increased due to NTK when compared to the control group. This study is distinctive because it directly responds to the needs of the foodservice industry, and the study output (NTK) can serve as the cornerstone to fill the gap in current food safety training for low-literacy or novice food handlers in the future.